The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physreva.93.063811
|View full text |Cite
|
Sign up to set email alerts
|

Electric dipole coupling in optical cavities and its implications for energy transfer, up-conversion, and pooling

Abstract: Resonant energy transfer, energy transfer upconversion, and energy pooling are considered within optical cavities to elucidate the relationship between exciton dynamics and donor/acceptor separation distance. This is accomplished using perturbation theory to derive analytic expressions for the electric dipole coupling tensors of perfect planar and rectangular channel reflectors-directly related to a number of important energy transfer processes. In the near field, the separation dependence along the cavity axi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The matrix element for energy pooling has an analogous form to Equation (35); the only difference is that the superscript m0 on A (which is now a donor) becomes 0n and the superscript 00 on M (now the acceptor) becomes s0, where s signifies a doubly excited molecule. In recent years, Lusk et al have demonstrated energy pooling experimentally [146] and discovered, among other advances, that the efficiency of energy pooling can be improved within a cavity [147][148][149]. Lately, moreover, they have studied the time-inverse mechanism of energy pooling, known as quantum cutting, which involves the excitation on A transferring to both D molecules [150].…”
Section: Recent Ret Research Nanomaterials For Energy Transfermentioning
confidence: 99%
“…The matrix element for energy pooling has an analogous form to Equation (35); the only difference is that the superscript m0 on A (which is now a donor) becomes 0n and the superscript 00 on M (now the acceptor) becomes s0, where s signifies a doubly excited molecule. In recent years, Lusk et al have demonstrated energy pooling experimentally [146] and discovered, among other advances, that the efficiency of energy pooling can be improved within a cavity [147][148][149]. Lately, moreover, they have studied the time-inverse mechanism of energy pooling, known as quantum cutting, which involves the excitation on A transferring to both D molecules [150].…”
Section: Recent Ret Research Nanomaterials For Energy Transfermentioning
confidence: 99%
“…Note that there is no space confinement for the propagating direction of the cavity modes, like waveguide modes. A previous study reported that the coupling factors of the cavity modes have 1/ R y dependence when kR y > 1 (far-field regime), and here we show how this evolves into the near field. A similar result is exhibited in the system with the transition dipoles of both the donor and the acceptor aligned along the y direction (Figure S4).…”
Section: Resultsmentioning
confidence: 85%
“…In addition to the RET enhancements along the cavity axis, the cavity modes also influence the RET along the direction parallel to the plane, , which is demonstrated in Figure d–f. Figure d considers the RET enhancement when the acceptor moves along the y direction, with Figure e showing the dependence of EF th on R y for the perfect cavity and Figure f showing that for the silver FP cavity.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34] However, there are ongoing debates stimulated by modern nanofabrication techniques, about controlling RET purely by means of the nanophotonic environment. Indeed, theory and experiments have revealed both enhanced and inhibited RET rates for many different nanophotonic systems, ranging from plasmonic systems to spasers.…”
Section: Introductionmentioning
confidence: 99%